Cushing's syndrome due to a non-adrenal ectopic adrenocorticotropin- secreting ewing's sarcoma in a child - (:unkn) unknown (Walter de Gruyter GmbH, 2009)
Ectopic ACTH syndrome (EAS) is extremely rare in the pediatric age group. Sarcomatous tumors causing EAS are even rarer. We report a 9 year-old girl presenting with Cushing's syn-drome caused by ectopic ACTH production by a Ewing's sarcoma. This case illustrates that rapid appearance of Cushingoid symptoms, absence of growth retardation and the presence of hypo-kalemia are suggestive clues for ectopic ACTH production as the source of Cushing's syndrome. © Freund Publishing House Ltd., London.
Keywords: Cushing's syndrome; Ectopic ACTH; Ewing's sarcoma; PNET